2005
DOI: 10.1002/jrs.1369
|View full text |Cite
|
Sign up to set email alerts
|

Self‐assembled monolayers of inositol hexaphosphate on the roughened surface of an iron electrode: investigation by surface‐enhanced Raman scattering spectroscopy

Abstract: Inositol hexaphosphate (IP 6 ) molecules as an environmentally friendly inhibitor were self-assembled at a bare iron surface forming monolayers from a low concentration solution. Roughening of the iron surface by a special oxidation-reduction cycle makes it possible to obtain surface-enhanced Raman scattering (SERS) mapping spectra of the self-assembled monolayers (SAMs) of IP 6 . Using the recorded SERS spectra and quantum chemistry calculations for the vibrational modes of the IP 6 molecule with the PM3 meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…42 Further studies reporting enhancement of the Raman signal on electrode surfaces were: hydrogen peroxide electroreduction on a Pb-modified Au electrode, 43 electronic effects in SERS by liquid water, 44 ex situ and in situ SERS analyses of polybithiophene using roughened Ag and Cu electrodes and multilayer SERS-active systems, 45 self-assembled monolayers of inositol hexaphosphate on the roughened surface of an iron electrode, 46 potential dependent SERS profiles of sulfanilamide, 47 of sulfanilic acid, 48 and of orthanilic acid 49 on silver electrode. Organic monolayers or thin films formed on the electrode surfaces are of great interest for both fundamental and practical reasons, especially as an effective technique for surface modification and self-assembly.…”
Section: Studies On Electrodesmentioning
confidence: 99%
“…42 Further studies reporting enhancement of the Raman signal on electrode surfaces were: hydrogen peroxide electroreduction on a Pb-modified Au electrode, 43 electronic effects in SERS by liquid water, 44 ex situ and in situ SERS analyses of polybithiophene using roughened Ag and Cu electrodes and multilayer SERS-active systems, 45 self-assembled monolayers of inositol hexaphosphate on the roughened surface of an iron electrode, 46 potential dependent SERS profiles of sulfanilamide, 47 of sulfanilic acid, 48 and of orthanilic acid 49 on silver electrode. Organic monolayers or thin films formed on the electrode surfaces are of great interest for both fundamental and practical reasons, especially as an effective technique for surface modification and self-assembly.…”
Section: Studies On Electrodesmentioning
confidence: 99%
“…Among the previous studies, compounds with the phosphoric functional group were considered to be one of the most effective chemicals for inhibiting the corrosion of iron. Yang et al found that inositol hexaphosphate molecule (IP 6 ), which was an environmentally friendly inhibitor, self-assembled on a bare iron surface from a low concentration solution . The adsorption configuration of IP 6 SAMs was deduced by using surface-enhanced Raman scattering spectra and quantum chemistry calculation.…”
Section: Introductionmentioning
confidence: 99%